Switchable absorptive bandstop to bandpass filter using stepped-impedance dual mode resonator - Zahari, M.K. (Universiti Teknikal Malaysia Melaka, 2017)
In this paper, a new switchable absorptive bandstop to bandpass filter using stepped-impedance dual mode resonator is proposed. This switchable filter provides two modes of operation which is absorptive bandstop and bandpass response. The first part of this paper presents a theoretical analysis of the absorptive bandstop filter using stepped-impedance dual mode resonator. The absorptive bandstop response can be achieved by connecting λ/4 length with the stepped-impedance dual mode resonator with correct diameter and position of via hole as an inductive element. The second part of this paper presents an investigation and design of the switchable absorptive bandstop to bandpass filter. PIN diodes are used as the switching element. The selectivity of the bandpass response can be improved by using extended via hole. The parametric studies together with the EM simulation of the new switchable absorptive bandstop to the dual mode bandpass filter is presented in this paper.